STRATEGIC INFORMATION SYSTEM PLANNING AND INFORMATION TECHNOLOGY - Agus Susilo Nugroho; Wing Wahyu Winarno; Hanif Al fatta (Literasi Nusantara, 2021)
For private vocational schools such as SMK At-Thoat Toroh, the acquisition of new students is very important. Because the number of students has a direct effect on the sustainability of the school. In obtaining new students, SMK At-Thoat Toroh not only competes with fellow private SMK / SMA / MA, but also public SMK / SMA / MA. There needs to be an increase in competitiveness in acquiring new students at SMK At-Thoat Toroh. Because the trend of new student admissions at SMK At-Thoat Toroh has decreased, especially during the Covid-19 pandemic. The solution offered in this study for this problem is to formulate a strategic information system design and information technology using the Ward and Peppard method. Ward and Peppard's method is able to produce IS / IT strategies that are in line with business strategies. The first stage in applying this method in this research is the analysis of current conditions, both the organization as a whole and the IS / IT aspect. The next stage is an analysis of IS / IT needs in the future. The final stage is the preparation of IS / IT strategic steps. To analyze each of these stages, analysis tools are needed, namely: SWOT, critical success factor, Mc Farlan Strategic, PEST, IS / IT trends and value chains. The implementation of the Ward and Peppard method and their analysis tools, is able to identify and recommend IS / IT needs at SMK At-Thoat Toroh for the next 3 years. However, the resulting recommendations must be adjusted to the school budget.